Current status and perspectives for utilization of DNA based marker technology in floricultural crops – A review - SINGH, SIMRAT; BALA, MADHU; DUBEY, R.K.; KRITIKA PANT (Journal of Ornamental Horticulture, 2024)
Recent advancements in ornamental plant breeding heavily depend on exploiting the genetic diversity found in wild relatives to improve cultivated varieties. This has led to a surge in interest towards utilizing both introgression techniques and genetic engineering tools to enhance ornamental plants. Recent developments of molecular genetics have been made utilizing DNA- based markers for assessment of genetic diversity in ornamental crops and their wild relatives for development of novel varieties governed by target gene(s) of interest. Besides, the application of markers in quantitative trait loci's (QTLs) mapping, construction of genetic linkage maps and marker assisted selection (MAS) in flower crops have been presented. The manuscript highlights the recent developments and review in the potential utilization of molecular marker techniques in commercially important ornamental crops.